Dynamic Drill-rate Test Approach Appplied to a Pre-salt Case Study - Nascimento, A. [UNESP]; Elmgerbi, A.; Roohi, A.; Prohaska, M.; Thonhauser, G.; Mathias, M. H. [UNESP] (Society of Petroleum Engineers (SPE), 2015)
Pre-salt basins and its exploration have become more and more frequently mentioned over the years, not just for their potential reserves, but for the implicit challenges in terms of general operations (downstream and upstream) to be faced in order to make these fields effectively commercially viable. Several research efforts aimed at to addressing these related barriers, but still in the drilling optimization and efficiency discipline, as a known challenge, a considerably low drillability is experienced when drilling throughout the pre-salt carbonates itself. A lot of already known rate of penetration (ROP) modeling and Specific Energy (SE) studies have been developed and improved during the past 50 years, helping in post- and pre-operations analysis, allowing simulations and tendency estimations, enabling a better understanding of possible parameters and design combinations for operations optimization and efficiency enhancement. Pre-run tests may be a very important tool together with consequent interpretation and re-usage of the results to help in boosting optimization in operations. Thus, the main focus of this paper is to address a reverse engineering by evaluating specific well data and information, identifying gaps to boost rate of penetration for a pre-salt well case study, based on a drilling mechanics analysis proposing a new analysis methodology, by playing-back through a reverse engineering procedure the drill-rate test curves, exemplifying its impact in analysis with a more dynamic and real-time focus.
Keywords: drill-rate test; drillability; optimization; pre-salt; real-time monitoring; reverse engineering; ROP